Iniciativa popular na concretização do direito fundamental à democracia - Silva, Aurélia Carla Queiroga da (2013)
The Participatory Democracy is disseminated throughout the Principle of Popular Sovereignty. Since it spurs the participation of the people in the exercise of political power, it emerges as a conciliatory alternative to the Representative Regime - one of questionable legitimacy in account of the distortion it causes on the will of the public. It does so specially vis-à-vis the legislative, where the law is created. It s known that our Constitution (arts. 1º e 14, CF/88) provides for the means through which the members of the public may take part in the political process of the country, for it consecrates the plebiscite, the referendum and the popular initiative, all of them incipiently regulated by the Lei nº 9.709/98. It s our task, thus, to inquire, through deductive reasoning as well as the legal exegeses, the enforceability of the Popular Initiative as a means of popular emancipation, given that it enables the citizens to conscientiously participate in the public sphere. It has also an educational ethos which builds the capacity of individual to act, and, therefore, through thoughtful choices, enhance the legal system. Furthermore, the Lei da Ficha Limpa (LC nº 135/2010) surely represents a milestone in the Brazilian political history, since it accrued from a new way of social interaction allowed by the usage of communication technology on the pursuit of political morality. As a matter of fact, this bill is a clear example of how a legal act was legitimately proposed through Public Initiative. Hence, it s beneficial to actually make use of the Public Initiative, under the influence of the New Constitutional Hermeneutics, with a view to supporting social claims and promoting a dialogical relationship with the State in order to help it in the decisionmaking process. Thereat, we can achieve important civic spaces through which the fundamental right to democracy shall be materialized, tearing apart the old paradigms of inequality and, thus, promoting social justice